Validation of a simplified-geometry model of inhaled formoterol pharmacodynamics in asthmatic patients - Panunzi, Simona; Gaz, Claudio; Cibella, Fabio; De Gaetano, Andrea (Frontiers in Physiology, 2022)
PharmacoKinetics (PK) and PharmacoDynamics (PD) mathematical models of inhaled bronchodilators represent useful tools for understanding the mechanisms of drug action and for the individuation of therapy regimens. A PK/PD model for inhaled bronchoactive compounds was previously proposed, incorporating a simplified-geometry approach: the key feature of that model is a mixed compartmental and spatially distributed representation of the kinetics, with the direct computation of representative flow rates from Ohm’s law and bronchial diameter profiles. The aim of the present work is the enrichment and validation of this simplified geometry modeling approach against clinical efficacy data. The improved model is used to compute airflow response to treatment for each single virtual patient from a simulated population and it is found to produce very good fits to observed FEV1 profiles. The model provides a faithful quantitative description of the increasing degree of improvement with respect to basal conditions with continuing administration and with increasing drug dosages, as clinically expected.